Projetos escolares como espaço de formação colaborativa: experiência de uma escola pública da zona leste de São Paulo - Rosa, Evelyn Camponucci Cassillo (2017)
This research was designed to study school projects in the formation of collaborative groups of teachers. The main objective is to analyze with which assumptions, and in which ways the school projects gain the positivity attributed to them in the literature. It is stated that they contribute to formation when potentialize the creation of collaborative groups in the school, allow the development of the autonomy of the teachers in the elaboration of significant projects with their colleagues and involves the students in a team spirit, as active subjects, reflective and participatory. Considering the school context where teachers are, in their different professional life cycles, we assume that school projects allow the creation of collaborative groups that potentialize their job, changes in their practice, in order to re-signify the teaching of these teachers, contributing to their formation. This research is justified because the teachers involvement in the construction of new projects presents itself as a pleasant and productive activity, increasing the exercise of its autonomy and its motivation. This can re-signify their teaching and offer their critical formation, innovative and reflexive based on their reality in joint and collaborative actions. Utilizing qualitative methodology, whose instrument of data collection will be: documentary analysis, bibliographical survey and focal group. As theoretical references to address teacher formation and professional development, the follow authors are mentioned: Antonio Nóvoa (1999), Leonor Maria Tanuri (2000), Olgaíses Cabral Maués (2011), Rosa Maria Torres (2009) and Chistopher Day (2001) , and Henry A. Giroux (1999). For an analysis of school education projects, the following authors: Maria Carmen S. Barbosa and Maria da Graça S. Horn (2008); Jorge Avila de Lima (2002), Michael Fullan and Andy Hargreaves (2001), Rui Canário (2003), Alda Junqueira Marin, Luciana Maria Giovanni and Maria Regina Guarnieri (2009) to refer the collaborative groups in schools. As of today the studies developed in master's degree research that deals with the theme allow us to affirm that school projects greatly assist the continued formation of teachers as they develop actions that involve teachers, students and the school community starting from issues that they can develop strategies using existing resources and others that will be developed throughout the process, indicating, in this way, the accomplishment of a collaborative formation.